2020
DOI: 10.2147/copd.s221980
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluating Patient Preferences of Maintenance Therapy for the Treatment of Chronic Obstructive Pulmonary Disease: A Discrete Choice Experiment in the UK, USA and Germany</p>

Abstract: Introduction: With increasing availability of different treatments for chronic obstructive pulmonary disease (COPD), we sought to understand patient preferences for COPD treatment in the UK, USA, and Germany using a discrete choice experiment (DCE). Methods: Qualitative research identified six attributes associated with COPD maintenance treatments: ease of inhaler use, exacerbation frequency, frequency of inhaler use, number of different inhalers used, side effect frequency, and out-of-pocket costs. A DCE usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Reducing the number of inhalers required and frequency of use should improve treatment persistence and adherence, which could in turn improve clinical effectiveness and patient outcomes [ 4 , 5 ]. Fewer inhalers and reduced treatment complexity has been highlighted as a preferred treatment strategy for patients with COPD [ 6 , 7 ]. In addition, the use of multiple inhalers has been associated with more frequent errors in inhaler technique compared with therapy administered via a single inhaler [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the number of inhalers required and frequency of use should improve treatment persistence and adherence, which could in turn improve clinical effectiveness and patient outcomes [ 4 , 5 ]. Fewer inhalers and reduced treatment complexity has been highlighted as a preferred treatment strategy for patients with COPD [ 6 , 7 ]. In addition, the use of multiple inhalers has been associated with more frequent errors in inhaler technique compared with therapy administered via a single inhaler [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…dose release, preparation, etc. ), Indicates empty (n = 1), Reusability (n = 2), Technology (n = 1 ) [ 15 , 23 , 25 , 29 , 30 , 32 , 33 , 35 , 36 , 42 , 49 ] 11 (39) 6 (32) 8 (67) Treatment cost [ 24 , 27 , 29 , 31 – 38 , 41 , 42 , 48 50 , 53 ] 17 (61) 12 (63) 7 (58) Other [ 24 , 28 , 30 , 33 , 35 , 42 , 43 , 48 , 50 , 53 ] 10 (36) 8 (42) 4 (33) Other: Treatment Class of compound (n = 1), Patient satisfaction (n = 1) [ 42 ] 1 (4) 0 (0) 1 (8) Other: Evidence Evidence of compliance (n = 1), Duration of evidence (n = 1), FDA approval (n = 1) [ 30 , 42 , 50 ] 3 (11) 2 (11) 1 (8) ...…”
Section: Resultsmentioning
confidence: 99%
“…Eight (29%) studies were conducted in both the US and the UK, with several others conducted in Australia ( n = 4, 14%), France ( n = 3, 11%) [ 25 , 29 , 42 ], Germany ( n = 3, 11%) [ 36 , 42 , 47 ] and the Netherlands ( n = 3, 11%) [ 26 , 38 , 53 ]. No studies were conducted in South America, Africa or Asia, meaning that no evidence is currently available on stakeholders’ preferences across those regions.…”
Section: Discussionmentioning
confidence: 99%
“…This poor compliance may particularly reflect challenges in complying with multiple-inhaler regimens in general. Indeed, up to 65% of patients with COPD from the US, Germany, and the UK preferred a once-daily single-inhaler regimen over a twice-daily dual-inhaler regimen [ 26 ]. Likewise, a US study reported a significantly higher discontinuation rate with multiple-inhaler COPD therapy than single-inhaler COPD therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%